TEACHER SKILLS IN GUIDING DISCUSSION IN CENTURY LEARNING 21 - Achmad Ali Fikri; Atmim Nurona; Latifatus Saadah; Lin Eflina Nailufa; Viki Ismah (TANJAK, 2021)
Skills to guide small group discussions conducted by teachers in 21st century learning , using descriptive methods in qualitative research. Descriptive method in research is research for the purpose of explaining or describing events, objects, circumstances, or variables that are explained using numbers and words. Type a descriptive method in research qualitative is a kind of library research ( library research ) literature documents from various sources related to the keter. Visible lead small group discussions conducted by the teacher in the 21st century learning. The skill of guiding small group discussions conducted by the teacher is the teacher trainee skills In teaching activities there are times when conducting group discussion activities. Discussion activities involve mental and emotional activities that can improve the ability of relationships between individuals. So that teachers' skills in guiding small group discussions are needed to ensure the continuity of discussions effectively. In this study, the learning environment was developed to skills of critical thinking and problem solving, collaboration, and communication , creativity and innovation. Skills include 21st century skills.